Respon Rumput Benggala (Panicum maximum L.) terhadap Gypsum dan Pupuk Kandang di Tanah Salin - Endang Dwi Purbajanti; Djoko Soetrisno; Eko Hanudin; Subur Priyono Sasmito Budhi (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2010)
The research was aim at studying the effect of application of gypsum and manure to growth, biomass yield, dry matter yield, dry matter content and crude protein of Benggala grass. This study used factorial design with nine replications. The first factor was manure dosages i.e. 0 and 20 ton ha-1. The second factor was gypsum dosages i.e. 0, 0.75, 1.5 and 3 ton ha-1. Variables to observe were relative growth rate (RGR), biomass yield, dry matter yield, dry matter content and crude protein. The application of 20 ton manure and 3 ton gypsum per hectare resulted the highest values of  RGR, biomass yield, dry matter yield, dry matter content and crude protein; they were 0.86 g day-1, 1039.4 g pot-1, 219.1 g pot-1, 20.9% and 8.1%, respectively. Response of RGR, biomass yield, dry matter yield, dry matter content and crude protein to gypsum application with 20 ton manure  ha-1 were linier.  Keywords :  benggala grass,  saline soil, gypsum, manure, nitrogen.